Basic and clinical pharmacology - Katzung, Bertram G;Trevor, Anthony J (New Delhi : McGraw-Hill Education, 2015)
Organized to reflect the course sequence in many pharmacology courses and in integrated curricula, Basic & Clinical Pharmacology covers the important concepts students need to know about the science of pharmacology and its application to clinical practice. Selection of the subject matter and order of its presentation are based on the authors' many years of experience in teaching this material to thousands of medical, pharmacy, dental, podiatry, nursing, and other health science students. Coverage that spans every aspect of medical pharmacology, including botanicals and over-the-counter drugs, and pharmacogenomics with examples. Emphasis is placed on discussion of drug groups and prototypes. Includes sections that specifically address the clinical choice and use of drugs in patients and the monitoring of their effects. Case studies introduce clinical problems in most chapters. Summary tables and diagrams encapsulate important information. A generic name/trade name table appears at the end of most chapters for easy reference when writing a chart order or prescription
A Lange medical book.
Includes bibliographical references and index
Keywords: Clinical pharmacology -- Pharmacology; Pharmacology -- Pharmacology, Clinical